Clonal Hematopoiesis, a Risk Condition for Developing Myeloid Neoplasia - Ugo Testa; Germana Castelli; Elvira Pelosi (Hemato)
Clonal hematopoiesis (CH) is an age-related process in which hematopoietic stem/progenitor cells increase their fitness due to the acquisition of mutations that lead to a proliferative advantage and to clonal expansion. Its frequency increases with age, and it mostly affects people older than 70 years. The most mutated genes in CH are epigenetic regulators, DNA damage response genes, and splicing factors, which are all involved in the development of myeloid neoplasia. Some risk factors, including age, smoking, and prior cytotoxic therapy, increase the risk of developing CH or increase the fitness of CH. Various types of CH have been observed, associated or not with cytopenias or monocytosis. CH represents a risk factor for many pathological conditions and particularly for hematologic malignancies. A better understanding of the risks related to CH has triggered the development of research, translational, and clinical programs for the monitoring, prevention, and treatment of CH.